2013
DOI: 10.1017/s0033291713000883
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use and first-episode psychosis: relationship with manic and psychotic symptoms, and with age at presentation

Abstract: Effective interventions for reducing cannabis use may yield significant health benefits for patients with first-episode psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 29 publications
(45 reference statements)
3
37
3
2
Order By: Relevance
“…However, among lifetime cannabis users in our sample, frequent cannabis use, early age of first use, and continued use over the UHR follow-up period were all associated with increased risk of transition to psychosis. These findings support our secondary hypotheses and are consistent with data from another study in UHR participants (Kristensen & Cadenhead, 2007) and studies of cannabis use in first-episode psychosis samples (Di Forti et al 2009;Gonzalez-Pinto et al 2011;Stone et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, among lifetime cannabis users in our sample, frequent cannabis use, early age of first use, and continued use over the UHR follow-up period were all associated with increased risk of transition to psychosis. These findings support our secondary hypotheses and are consistent with data from another study in UHR participants (Kristensen & Cadenhead, 2007) and studies of cannabis use in first-episode psychosis samples (Di Forti et al 2009;Gonzalez-Pinto et al 2011;Stone et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…A dose-response relationship between the pattern of use and psychotic symptoms or psychosis has also been reported, with heavier use increasing the risk (van Os et al 2002;Di Forti et al 2009). Continued use after the onset of psychosis is linked to poorer outcomes (Gonzalez-Pinto et al 2011;Stone et al 2014). Several studies have found that cannabis is more likely to be associated with psychosis-like experiences in people who have an existing predisposition, on account of having subclinical psychotic experiences (van Os et al 2002;Henquet et al 2005) or a family history of psychosis (Miller et al 2001;Stowkowy & Addington, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, while some evidence suggests that discontinuation of cannabis use may lead to a reduction in readmission rates 21,22 and improvement in symptomatic and functional outcome of psychosis 15,[22][23][24][25][26] , others suggest that this may not necessarily be the case 1,10,27,28 . Although, about 30-50% of cannabis users stop using it after the onset of their psychotic illness 15,[21][22][23]29 suggesting that this may be a clinically relevant issue worth exploring, there is lack of clarity in terms of existing evidence as outlined earlier. Furthermore, conclusions from the individual studies need to be treated with caution in light of the relatively modest sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of how important cannabis use is in causing the onset of schizophrenia, it is fairly clear that continued cannabis use after diagnosis is associated with more severe positive symptoms and decreased functioning in both first episode and more chronically ill people with schizophrenia [5], and that discontinuing cannabis use improves mood and anxiety symptoms [38], psychotic symptoms [39], and psychosocial functioning [38].…”
Section: Vulnerability Factorsmentioning
confidence: 99%